Analysis of the Implementation of Internal Control Based on COSO 2013 in the Service Payment Requirement Document Verification Process at PT PLN (Persero) UP3 Yogyakarta - Cindy Berliane Ristanti; Sri Mulyati (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the implementation of internal control based on the COSO 2013 framework in the verification process of service payment requirement documents at PT PLN (Persero) UP3 Yogyakarta and to examine its role in preventing potential irregularities in cash disbursements. This issue is important because service payment transactions involve company funds and require adequate control to ensure accountability, accuracy, and compliance with applicable procedures. The study employed a qualitative descriptive approach. Data were collected through in-depth interviews with relevant informants. The findings show that internal control has been implemented effectively through clear clear duties, layered verification, VIP systems, communication, and monitoring, ensuring accountable cash disbursement management. The Document verification prevents cash disbursement irregularities by reducing errors, fraud, and unauthorized payments.